The Black Butterfly : Brazilian Slavery and the Literary Imagination - Wood, Marcus (Book collections on Project MUSE., 2019)
"The Black Butterfly focuses on the slavery writings of three of Brazil's literary giants--Machado de Assis, Castro Alves, and Euclides da Cunha--from the late nineteenth and early twentieth century"--